Poziom nasycenia organizacji zarządzaniem wiedzą - próba definicji - Tabaszewska, Edyta (Standard of saturation of an organization in knowledge management - an attempt of definition, 2007)
The aim of the paper is an attempt at defining standard of saturation of an organization in knowledge management. In author’s opinion, every organization applies the knowledge management, and the standard of saturation in this conception depends on standard of knowledge management, standard of spread its principles and tools among the employees and organizational culture. The type of business and size of organization also has an influence on this standard.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 266-274